لێهاتووییەکانی ژیان و پەیوەندییان بە فشاری دەروونییه‌وه‌ لای مامۆستایانی باخچەی منداڵان لە شاری سلێمانی - عبدالله, م. د.فرمان زاهر; قادر, بنار بهاءالدین حەمە (Sulaimani Journal for Humanities, 2023)
The aim of the study was to determine the level of life skills and stress among kindergarten teachers, as well as to determine the relationship between life skills and stress among kindergarten teachers, and find statistical differences in the level of life skills and stress among kindergarten teachers according to: gender, years of experience, residence. The scope of the study includes kindergartens in the center of Sulaimani, for the academic year (2021-2022), the sample of the study was kindergarten teachers in the center of Sulaimani, which numbered (225) teachers of male and female. The researcher used the descriptive method to achieve the objectives of this study, where the research tools consisted of life skills and stress scales. The researcher benefited from scientific sources and previous researches to prepare the life skills scale which consisted of (44) items, and to prepare the stress scale, the researcher used both criteria of (sleman, 2015) and (Al-Amriya, 2014) which consisted of (30) items according to the steps of preparing scientific criteria, after extracting the validity and reliability for each of the criteria. The researcher used (SPSS) program. In light of the analysis of the results, the researcher reached the following conclusions: 1. The level of life skills among kindergarten teachers is generally high. 2. The level of stress among kindergarten teachers is generally low. 3- There is a statistically documented negative relationship between life skills and stress in the view of kindergarten teachers in the center of Sulaimani, which means that there is an inverse relationship between life skills and stress.